Electromagnetic deformable mirror fabricated using silicon micromachining and stress-resilient assembly - Man, Wenkuan (Kevin); Bifano, Thomas (Advanced Optical Technologies, 2025)
Introduction: This work presents a prototype electromagnetic actuation deformable mirror (DM) assembly with stress-resilient face sheet design.Methods: The DM face sheet design includes slender micromachined silicon pillars that are integrated with a silicon face sheet to reduce unpowered face sheet surface distortion caused by actuator adhesion stress.Results: The assembled deformable mirror prototype allowed bi-directional actuation with total stroke exceeding 20 μm. A two-step control method was used to improve the prototype dynamic performance, allowing settling time on the order of 1 ms. Prescribed references shapes were made on the prototype deformable mirror using closed-loop control.Discussion: While the simplified DM produced in this work has only 19 actuators and therefore has limited capacity to control complex shapes, the design and fabrication processes described and demonstrated in this work provide a promising approach to development of high-stroke magnetic DMs.